Analisis Kesantunan Berbahasa Netizen Indonesia di Era Digital pada Aplikasi Twitter (X) - Nurinayah, Nurinayah; Anshari, Anshari; Usman, Usman (Nuances of Indonesian Language, 2025)
This study aims to describe the politeness of Indonesian netizens' language in the 2023 comments section of the Twitter (X) accounts @aniesbaswedan, @prabowo, and @ganjarpranowo, based on Leech's politeness scales: cost-benefit scale, optionality scale, indirectness scale, authority scale, and social distance scale. The method employed in this research is a qualitative descriptive approach. Data were collected using library research, observation, and note-taking techniques. The analysis techniques used include (1) Identification, (2) Coding, (3) Classification, (4) Analysis, and (5) Discussion. The findings reveal that Indonesian netizens' digital politeness on social media Twitter (X) in 2023 is still often neglected. Out of 195 utterances analyzed, 91 were deemed polite, while 104 were impolite. On the cost-benefit scale, polite utterances involved support and prayers for the interlocutors, while impolite utterances consisted of demands or orders directed, opinions, suggestions, or feedback delivered in harsh language. On the optionality scale, many impolite utterances occurred due to the absence of options or opportunities given to the interlocutor. On the indirectness scale, numerous impolite utterances were found to insult and belittle the interlocutor. On the authority scale, polite utterances included hopes and support for the interlocutor regarding their positions. In contrast, impolite utterances consisted of harsh criticism of the performance of the interlocutor. On the social distance scale, polite utterances consisted of encouraging words, hopes, and prayers for the interlocutors, while impolite utterances used overly familiar terms that disrespected the interlocutors, slang, and harsh language.